Examining the UK Stock Market Reaction to Earnings Announcements: An Empirical Test of Market Efficiency - Hubbard, Charles (2021)
Whilst many studies have examined the efficiency of the US stock market reaction to earnings announcements there is a significant gap in the literature for the UK stock market, particularly in recent years. The major aim of this study is to examine whether the stock market reacts efficiently to earnings announcements, and test whether the post-earnings announcement drift phenomenon is present in the UK for the years 2014-2019. The minor aims of this study are to investigate whether the stock price reactions to earnings announcements are influenced by factors such as the magnitude of the earnings surprise, firm size, and capital structure.